2016
DOI: 10.1111/ced.12937
|View full text |Cite
|
Sign up to set email alerts
|

The -2518 A/GMCP-1and -403 G/ARANTESpromoter gene polymorphisms are associated with psoriasis vulgaris

Abstract: The results of our analysis suggest that the -2518 A/G MCP-1 and -403 G/A RANTES promoter gene polymorphisms may be risk factors for psoriasis and may influence its clinical presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
(34 reference statements)
0
10
0
1
Order By: Relevance
“…Multiple studies have been performed to detect the polymorphisms as an important factor in the development of psoriasis: TNF α gene -238G/A polymorphism [ 27 ] -2518 A/G MCP-1 and -403 G/A RANTES promoter gene polymorphisms [ 28 ], CARD14 rs11652075 polymorphism [ 29 ] and support the genetic hypothesis in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been performed to detect the polymorphisms as an important factor in the development of psoriasis: TNF α gene -238G/A polymorphism [ 27 ] -2518 A/G MCP-1 and -403 G/A RANTES promoter gene polymorphisms [ 28 ], CARD14 rs11652075 polymorphism [ 29 ] and support the genetic hypothesis in psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…With genotyping of hundreds of thousands of polymorphisms it led in the last decade to identification of novel genetic risk markers associated with psoriasis. The latest results of genetic analyses including patients with psoriasis from northern Poland have demonstrated the association of the –2518 A/G monocyte chemoattractant protein-1 ( MCP-1 ) and –403 G/A regulated on activation, normal T-cell expressed and secreted ( RANTES ) promoter gene polymorphisms with an increased risk of psoriasis and suggested the influence of polymorphisms in the Toll-like receptor 2 ( TRL2 ) and Toll-like receptor 9 ( TLR9 ) genes on the clinical manifestation of this dermatosis [ 31 , 32 ]. Among different genetic markers identified in the context of psoriasis susceptibility, HLA-C*06 still presents the strongest association with the early-onset type of the disease in Caucasians [ 3 , 7 , 8 , 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our data analyses, the polymorphism rs1024611 in MCP1 did not show any association with PV susceptibility in genotype or allele. However, in the study by Zablotna et al, [ 20 ] MCP1 rs1024611 polymorphism was found to be significantly associated with the increased risk of PV in northern Poland. Such difference may result from the distribution difference of the polymorphism, different ethnicity, and sample size.…”
Section: Discussionmentioning
confidence: 92%